Psychosocial factors associated with change in pain and disability outcomes in chronic low back pain patients treated by physiotherapist: a systematic review - Alhowimel, Ahmed; Alotaibi, Mazyad; Radford, Kathryn A.; Coulson, Neil S. (SAGE Journals, 2018)
Background: Almost 80% of people have low back pain at least once in their life. Clinical guidelines emphasize the use of conservative physiotherapy and the importance of staying active. While the psychological factors predicting poor recovery following surgical intervention are understood, the psychosocial factors associated with poor outcomes following physiotherapy have yet to be identified. Methods: Electronic searches of PubMed, Medline, CINAHL, PsycINFO and EBSCO were conducted using terms relating to psychosocial factors, chronic low back pain, disability and physiotherapy. Papers examining the relationship between psychosocial factors and pain and disability outcomes following physiotherapy were included. Two reviewers selected, appraised and extracted studies independently. Results: In total, 10 observational studies were identified that suggested an association between fear of movement, depression, self-efficacy and catastrophizing in modifying pain and disability outcomes following physiotherapy. Discussion: Although limited by methodological shortcomings of included studies, and heterogeneity of physiotherapy interventions and measures of disability and psychosocial outcomes, the findings are consistent with other research in the context of back pain and physiotherapy, which suggest an association between psychosocial factors, including fear of movement, catastrophizing and self-efficacy and pain and disability outcomes in chronic low back pain patients treated by physiotherapist. However, a direct relationship cannot be concluded from this study. Conclusion: Findings suggest an association between psychosocial factors, including fear of movement, catastrophizing and self-efficacy and pain and disability outcomes in chronic low back pain patients treated by physiotherapist, which warrants further study.